2013
DOI: 10.1038/srep02143
|View full text |Cite
|
Sign up to set email alerts
|

All-Versus-Nothing Proof of Einstein-Podolsky-Rosen Steering

Abstract: Einstein-Podolsky-Rosen steering is a form of quantum nonlocality intermediate between entanglement and Bell nonlocality. Although Schrödinger already mooted the idea in 1935, steering still defies a complete understanding. In analogy to “all-versus-nothing” proofs of Bell nonlocality, here we present a proof of steering without inequalities rendering the detection of correlations leading to a violation of steering inequalities unnecessary. We show that, given any two-qubit entangled state, the existence of ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 25 publications
2
72
0
2
Order By: Relevance
“…Recently, an inequality to delineate quantum steering from other non-local properties was proposed [4][5][6] and tested in a range of experiments [6,7]. Steerability has since then been further investigated with all-versus-nothing measures [8], and has been utilized as a way to characterize and visualize the state-space of two-qubit systems [9]. In combination these different concepts (Bell non-locality, steerability, and entanglement) form a hierarchy and enable one to categorize different non-local properties of quantum states.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an inequality to delineate quantum steering from other non-local properties was proposed [4][5][6] and tested in a range of experiments [6,7]. Steerability has since then been further investigated with all-versus-nothing measures [8], and has been utilized as a way to characterize and visualize the state-space of two-qubit systems [9]. In combination these different concepts (Bell non-locality, steerability, and entanglement) form a hierarchy and enable one to categorize different non-local properties of quantum states.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the fundamental theorem has achieved ubiquitous applications in different quantum information tasks, such as quantum key distribution [5], communication complexity [6], and random number generation [7].Unlike quantum entanglement and Bell's nonlocality, the research field of quantum steering has been sterile till 2007, when Wiseman, Jones, and Doherty [8] reformulated the idea and placed it firmly on a rigorous ground. Since then EPR steering has gained a very rapid development in both theories [9][10][11][12][13][14][15]17] and experiments [18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that violation of a steering inequality is necessary for one-sided device-independent quantum key distribution [16]. EPR steering admits an asymmetric formulation: there exist entangled states which are one-way steerable, i.e., demonstrate steerability from one observer to the other observer but not vice-versa [17,18]. Various other steering criteria have also been proposed such as all versus nothing proof of EPR steering [17] and hierarchy of steering criteria based on moments [19].…”
Section: Introductionmentioning
confidence: 99%
“…EPR steering admits an asymmetric formulation: there exist entangled states which are one-way steerable, i.e., demonstrate steerability from one observer to the other observer but not vice-versa [17,18]. Various other steering criteria have also been proposed such as all versus nothing proof of EPR steering [17] and hierarchy of steering criteria based on moments [19]. Motivated by the question of how much a steering scenario demonstrates steerability, a measure of steering called steering weight was defined in Ref.…”
Section: Introductionmentioning
confidence: 99%